2003
DOI: 10.1038/sj.leu.2402800
|View full text |Cite
|
Sign up to set email alerts
|

Effect of imatinib on haematopoietic recovery following idarubicin exposure

Abstract: SCF is a potent pro-proliferative cytokine crucial for haematopoiesis, which binds to c-kit and activates its tyrosine kinase activity. Inactivating mutations of either SCF or c-kit have been described in mice and lead to increased sensitivity to treatment with ionising radiation. Imatinib is a tyrosine kinase inhibitor with high affinity for c-Abl, PDGFR and c-kit. In this study we investigated the effect of concomitant administration of imatinib and idarubicin, an anthracycline with haematosuppressive activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…Interestingly, a very high doxorubicin accumulation was observed in the spleen of the free doxorubicin treated mice (Figure d). This was consistent with a significant loss of spleen weight (Figure c), and histopathological analysis confirmed lymphocyte depletion in the periarteriolar lymphoid sheaths, with shrinkage of both the medulla and marginal zones of secondary follicles (Supporting Information, Figure 2) typical of doxorubicin-induced hematopoietic toxicity. , Furthermore, treatment with doxorubicin also resulted in significant loss of cardiac mass, consistent with cardiotoxicity reported with doxorubicin treatment . Interestingly, significantly elevated levels of doxorubicin were observed in the tumor following treatment with fullerenol- or single-walled CNT-conjugated doxorubicin as compared with free doxorubicin (Figure d).…”
Section: Resultssupporting
confidence: 79%
“…Interestingly, a very high doxorubicin accumulation was observed in the spleen of the free doxorubicin treated mice (Figure d). This was consistent with a significant loss of spleen weight (Figure c), and histopathological analysis confirmed lymphocyte depletion in the periarteriolar lymphoid sheaths, with shrinkage of both the medulla and marginal zones of secondary follicles (Supporting Information, Figure 2) typical of doxorubicin-induced hematopoietic toxicity. , Furthermore, treatment with doxorubicin also resulted in significant loss of cardiac mass, consistent with cardiotoxicity reported with doxorubicin treatment . Interestingly, significantly elevated levels of doxorubicin were observed in the tumor following treatment with fullerenol- or single-walled CNT-conjugated doxorubicin as compared with free doxorubicin (Figure d).…”
Section: Resultssupporting
confidence: 79%
“…Based on already published results, cardiotoxicity or neutropenia should be taken into account when STI571 and DOX are considered in combined treatment. In mice treated with STI571 in combination with idarubicin, another anthracycline derivative, a more severe neutropenia was induced when compared with that of mice treated with idarubicin alone (Ruchatz et al, 2003). It is well known that cardiomyopathy and congestive heart failure could be developed after completion of cumulative anthracycline regimens (Steinherz et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relatively high specificity of IM treatment towards the BCR-ABL fusion protein, off-target multikinase inhibitory effects occur and can interfere with normal hematopoiesis. 1, 2 For instance, non-specific inhibition of Flt3L has been associated with disruption of dendritic cell (DC) homeostasis and functions in both mice and humans. 3 In addition, studies have reported an interference of IM with T cell counts and activation.…”
Section: Introductionmentioning
confidence: 99%